South Africa's water heritage and its future preservation: establishing a water research archive for water-related information sources - Van der Walt, T. B.; Schellnack-Kelly, I. S. (Faculty of the Humanities, University of the Free State, 2015)
Archives and records are the tools that facilitate transparency, accountability and preserve collective social memory. They provide the mirror revealing governance, providing administrative and technical measuring instruments to ascertain the contexts and consequences of intended objectives, such as the promulgation and execution of water related policies. South Africa faces a water crisis and concerns exist about the governance of water affairs. Concerns and prospects for the creation of a water archive have been recommended. The prospects that such an initiative could provide is for better care and preservation of water-related records, including records on water services, water conservation and demand management currently across national government, municipalities and twelve water boards. The concept of the archives being an area storing dusty documents is being transformed, with the aid of technology. Through the digital environment, an archive can integrate hardcopy and digital material in a sustainable manner, accessible to a wide-range of researchers both within the archival institution and virtually to a different place and time zone. A dedicated “water archive” capturing and preserving water related information sources would provide water sector managers, engineers, scientists, researchers and administrators, with effective access to water-related information sources, as well as opportunities to contribute to the sustainability and further expansion of this archive.
Keywords: Records management; Digital records; Governance; Water archives; Archival collections; Heritage